Analysis of the Implementation of the Criminal Procedure Code in Handling Cyber Crimes: Between Effectiveness and Justice - Sari, Ratih Mega Puspa (Jurnal Hukum dan Keadilan, 2025)
The development of digital technology has given rise to various forms of cybercrime that challenge the criminal procedure system in Indonesia. This study aims to analyze the implementation of the Criminal Procedure Code (KUHAP) in handling cybercrimes, with a focus on effectiveness and justice. The method used is a descriptive qualitative approach through in-depth interviews with investigators, prosecutors, judges, and criminal law academics, accompanied by a documentary study of the Criminal Procedure Code (KUHAP), the ITE Law, and related court decisions. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawing/verification, and its validity was tested using the triangulation method of sources, methods, and time. The results of the study indicate that the application of the Criminal Procedure Code (KUHAP) in cyber cases still uses a conventional legal framework that is not fully adaptive to the characteristics of digital crimes. The effectiveness of criminal procedure law in the cyber context is still limited by technical and normative obstacles, while the aspect of justice is only fulfilled at the procedural level, not substantive. This study recommends the need for an update to the KUHAP based on a digital justice system to ensure a balance between effective law enforcement and substantive justice in the information technology era.